Manfaat Penggunaan Mobile Health sebagai Strategi Intervensi Mengurangi Efek Samping Kemoterapi pada Pasien Kanker - Hutagaol, Rutmauli; Sari, Kartika Mawar; Fratama, Ferry Fadli (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to analyze the application of mHealth-based interventions to the side effects of treatment in patients undergoing chemotherapy treatment. The method used is a systematic review of 4 databases, Sciendirect, Pro Quest, CINAHL, Pubmed, and Scopus, published from 2017 to 2022. This study's results show that using mHealth in patients undergoing chemotherapy can reduce symptoms of nausea and vomiting, conserve energy, reduce neuropathic symptoms, improve healthy behavior in cancer patients, and reduce the incidence of mucositis and difficulty opening the mouth. Reducing complaints of nausea and vomiting is the most significant benefit of using mHealth. This is associated with complaints of nausea and vomiting, which occur most frequently in cancer patients undergoing chemotherapy. In conclusion, using mHealth as a technology-based intervention strategy can reduce side effects in patient care, especially the side effects of chemotherapy treatment. There is a need to use mobile health interventions to reduce the side effects of chemotherapy. Keywords: Side Effects of Chemotherapy, Cancer, Mobile Health